2012
DOI: 10.3390/medicina48100074
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of HBME-1, E-cadherin, and CD56 in the Differential Diagnosis of Thyroid Nodules

Abstract: Background and Objective. Distinction between benign and malignant thyroid tumors is essential for proper clinical management. The aim of this study was to evaluate the diagnostic potential of a set of 3 molecular markers in the differential diagnosis of thyroid tumors. Material and Methods. Immunohistochemistry for HBME-1, E-cadherin (E-CAD), and CD56 was carried out in 36 follicular adenomas, 77 colloid goiters, 36 papillary thyroid carcinomas, and 14 follicular carcinomas. Sixty-eight thyroid fine needle as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…[3] In the differentiation of thyroid lesions, cytokeratin 19 (CK19) and mesothelioma antibody (HBME-1: Mesothelioma ab-1) expressions were examined in many studies and significant results were obtained. [456] Similarly, there were studies showing that loss of CD56 expression in malignant thyroid lesions. [3567] CD56 is a neural cell adhesion molecule that is expressed in natural killer cells, activated T-lymphocytes, and neural and muscle tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] In the differentiation of thyroid lesions, cytokeratin 19 (CK19) and mesothelioma antibody (HBME-1: Mesothelioma ab-1) expressions were examined in many studies and significant results were obtained. [456] Similarly, there were studies showing that loss of CD56 expression in malignant thyroid lesions. [3567] CD56 is a neural cell adhesion molecule that is expressed in natural killer cells, activated T-lymphocytes, and neural and muscle tissue.…”
Section: Introductionmentioning
confidence: 99%
“…[456] Similarly, there were studies showing that loss of CD56 expression in malignant thyroid lesions. [3567] CD56 is a neural cell adhesion molecule that is expressed in natural killer cells, activated T-lymphocytes, and neural and muscle tissue. [89] Studies reported that CD56 expressed in normal thyrocytes, benign or malignant follicular lesions but not in PTC and had quite high sensitivity and specificity in differentiating PTC other follicular thyroid lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Correct pathological diagnosis is necessary to minimize emotional stress, over-treatments and related financial costs brought by the diagnosis of thyroid cancer [3]. In order to eliminate disagreements among pathologists about well-differentiated lesions of thyroid derived from follicular epithelial cells and achieve diagnostic standardization, there have been many studies made where immunohistochemical and molecular markers are studied [4,5,6,7,8,9,10,11,12]. The immunohistochemical markers Hector Battifora mesothelial cell epitope-1 (HBME-1), galectin 3 (Gal-3) and cytokeratin 19 (CK19) accepted to be indicators of malignancy in thyroid lesions have been used as products of such studies as panels in most pathology laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Currently, the gold standard for the diagnosis of thyroid lesions, particularly PC, is histology. Using morphological criteria, most papillary cancers can be diagnosed with ease, except cases in which there is a paucity of diagnostic nuclear features.…”
Section: Discussionmentioning
confidence: 99%